Kontribusi Pendapatan Usahatani Bunga Bahan Canang terhadap Pendapatan Rumah Tangga Petani di Kecamatan Banjarangkan, Klungkung - GAYATRI, DESAK MADE PRADNYA; SUSRUSA, KETUT BUDI; ANGGRENI, I GUSTI AYU AGUNG LIES (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism); Vol.11, No.2, Desember 2022DO - 10.24843/JAA.2022.v11.i02.p13, 2022)
Contribution of Canang Flower Farming Income to Farmer's Household Income in Banjarangkan District, Klungkung Balinese Hindu life can’t be separated from the consumption of flowers such as canang flowers. The income will contribute to farmer's household income so the contribution needs to be known. This study aims to determine: a) the income of canang flower using farming analysis methods, b) the source of household income by household income analysis, and c) the contribution of canang flowers income to household income by contribution of farming income analysis. The result showed that the income of canang flowers is Rp2.605.107/year/person for pacar air flowers, Rp39.626.893/year/person for gemitir flowers, and Rp12.267.678/year/person for both commodities. Sources of household income of farmers come from the income of canang flower, farming income other than canang flowers (plants and livestocks), and non-farming income. The contribution of canang flower income to farmers' household income is in the very low category, namely 23.58%. This showed that farmers do not rely on income from canang flower farming to meet their household needs. Training and mentoring of farmers, providing market information and the accuracy of fertilizer distribution are expected to increase farm productivity so it can increase income as well as its contribution.